Screening of Ranunculus sceleratus for enzyme inhibition, antibacterial and antioxidant activities (Bangladesh Journal of Pharmacology, 2015)
Enzyme inhibition potential of various fractions of Ranunculus sceleratus was checked against ?-glucosidase, butyrylcholinesterase, acetylcholinesterase and lipoxygenase enzymes. n-Butanol fraction showed very good activity (77.5 ± 1.0% inhibition at 0.1 mg/mL) against ?-glucosidase. Its IC50 value was 35.7 ± 1.0 µg/mL comparable to quercetin (IC50 value 16.5 ± 0.4 µg/mL). Antibacterial activity was checked against five bacterial strains by 96-wells microplate assay using ciprofloxacin, a standard antibiotic. Chloroform, ethyl acetate, n-butanol and aqueous fractions showed excellent activity against Pseudomonas aeruginosa, (MIC at 7.1, 7.8, 5.6 and 5.3 respectively), which is greater than standard antibiotic ciprofloxacin (MIC 10.0). The antioxidant potential of all the fractions was evaluated. Ethyl acetate soluble fraction exhibited highest percent inhibition of DPPH radical as compared to other fractions. It showed 80.9 ± 1.2% inhibition of DPPH radical at a concentration of 30 µg/mL. These results suggest that R. sceleratus is a valuable herb, which inhibits the oxidative stress mechanism that lead to degenerative diseases.